Workshop Menulis dan Membaca Geguritan di SMP Terpadu Ponorogo - Rohmat Djoko Prakosa Prakosa (Sekolah Tinggi Kesenian Wilwatikta (STKW) Surabaya, 2023)
Geguritan is a poem composed in Javanese words. The word gurit means composing, geguritan means essay, writing, song, song. The meaning of this lexican expands as geguritan means chanting, singing songs. This meaning is still valid in the oral tradition in Bali (in the Javanese literary tradition, geguritan has a narrower meaning, focused on interpreting geguritan as Javanese poetry). Workshop participants at the end of the activity have the ability to create Javanese literary works in accordance with their personal experience and the participants' familiarity with the everyday environment. This makes it easier for participants to compose the structure of everyday communication into beautiful language, namely geguritan.